EXPERIMENTAL AND NUMERICAL DETERMINATION OF THE WHEEL-RAIL ANGLE OF ATTACK - Dragan Milković; Goran Simić; Jovan Tanasković; Živana Jakovljević; Vojkan Lučanin (Facta Universitatis. Series: Mechanical Engineering, 2015)
Angle of attack is an important wheel-rail contact parameter. It serves for estimation of the rolling stock curving performance. Together with wheel-rail contact forces, angle of attack influences the wear index. This paper presents experimental on-track measurements of the angle of attack using a specially designed laser device installed on track. Experiments are performed on three types of rail vehicles: shunting locomotive series 631-301, motor unit 412-077 and trailing unit 416-077 of electromotor train 412/416. Experimental measurements are compared with multibody system (MBS) simulations using specialized computer package VAMPIRE Pro. We have found good agreement between the results obtained experimentally and by simulations. Using these data, we have also performed relative comparison of wear indices of the outer wheels of the leading wheelsets for each of the tested vehicles.